NON-CONTRACT LIABILITY OF THE EUROPEAN UNION MEMBER STATES - Hoca, Elif (International Scientific Journal Vision, 2020)
The European Union has succeeded in creating its own sui generis legal system within the period of political and economic integration. Due to the sui generis structure in question, the member states were obliged to transfer their sovereignty to the EU. In the line of the membership process, the candidates who want to take be as a part of the European Union, States admitted to the union according to EU law, at the national level are responsible for the systematic, correct and effective implementation of EU legal rules. This means responsibility towards the EU both in the Union and outside the Union. In this respect, upon the completion of the membership process, the members are obliged to fulfill the duties they have undertaken. Member states may face an infringement action that may be brought by the Commission or other member states before the Court of Justice of the European Union (CJEU) due to an action or inaction that violates the Union Law, which they accept with the membership. Besides, If individuals are harmed due to the act, according to the nature and degree of the violation in question, then rectification of this damage will appear. In case of such situations, the principle of state responsibility, which emerges depending on the decisions of the EU Court of Justice, plays a role in reaching a solution. The principle in question is an important legal instrument in terms of protecting the rights arising from Union law. Conditions regarding the contractual and non-contractual liability of member states are set out in the case-law of the CJEU.